(untitled) (Journal of Economic Research & Business Administration, 2016)
Theoretical bases of functionally-cost analysis are expounded in the article. Reveals the purpose, objectives and features of functional-cost analysis. Set its place and importance in the analysis system. Attention is paid to the development of teaching materials on the organization and conduct of functional-cost analysis. The basic difficulties faced by specialists during the functional-cost analysis. It identified the advantages and disadvantages of this method. Functional-cost analysis is a fundamental difference from the usual ways of reducing production and operating costs, as it provides a functional approach. The essence of this approach – consideration of the object is not in its concrete form, but as a set of functions that it must perform. Each of them is analyzed from the perspective of the possible principles and methods of execution by a set of special techniques. Evaluation of options for building object is made by the criterion that takes into account the degree of implementation and relevance of functions, as well as the size of the costs associated with their implementation at all stages of the life cycle.